Prevelance of hepatitis e virus in a cohort of imunocompromised egyptian patients - Abeer Abdel Samed Abdel Khalek; Walaa Abdel Fattah Attia (2020)
(3CXgQJ GdJMGdjd GdeNHQjI HeG aj Pdc GdgjehLehHjf(B, (3NdGjG GdOe GdHjVGA(B, (3GdUaGFM GdOehjI hcPdc GNJHG GQJ hXGFa GdcHO heSJhi GdcQjGJjfjf aj GdOe GNJdGaG egkeG EMUGFkjG Hjf GdeLehYGJ GdeOQhSI(B. (3heY Pdc(B, (3CXgQ GdYO GdeeaGhj(B, (3dG aQb EMUGFj Hjf GdeLehYGJ GdeOQhSI(B. (3aj GdeLehYI GdaQYjI ef eQVj RGQYI GdcHO(B, (3cGf GdYeQ CYei aj GdeQVi GdPjf jYGfhf ef GLSGe eVGOI GjLGHjI dajQhS GdJgGH GdcHO GdhHGFj (B)(3g(B(, (3ceG cGf eSJhi GdcQjGJjfjf CYei aj GdeQVi GdPjf jYGfhf ef GLSGe eVGOI GjLGHjI dajQhS GdJgGH GdcHO GdhHGFj (B)(3g(B(. (3heY Pdc(B, (3aEf GdeJZj GQJ GdCNQi HeG aj Pdc GdfhY(B, (3heOI GdRQY(B, (3hGNJHG GQJ hXGFa GdcHO(B, (3hGdCOhjI GdeKHWI deefGYI hJUeH GdcHO de JXgQ Cj aQb EMUGFj Hjf GdeQVi GdPjf jYGfhf ef GLSGe eVGOI GjLGHjI dajQhS GdJgGH GdcHO GdhHGFj (B)(3g(B(, (3ebGQfI eY ChdFc GdPjf djS dOjge GLSGe eVGOI dajQhS GdJgGH GdcHO GdhHGFj (B)(3g(B.( (3aj GdeLehYI GdaQYjI dajQhS fbU GdefGYI GdHTQjI(B, (3cGf GdMeV Gdfhhj GdQjHj GdajQhSj GdbGHd decTa CYei HTcd eeMhX aj GdeQVi GdPjf jYGfhf ef GLSGe eVGOI GjLGHjI dajQhS GdJgGH GdcHO GdhHGFj(B) (3g(B(. (3heY Pdc(B, (3aEf GdeJZj GQJ GdCNQi HeG aj Pdc GdYeQ hGdLfS hYOO NdGjG (BCD4 (3hGdMed GdajQhSj dajQhS fbU GdefGYI GdHTQjI hfJGFL GdJeja Yf WQjb GdJeja(B, (3CXgQJ YOe hLhO aQb EMUGFj Hjf GdeQVi GdPjf jYGfhf ef GLSGe eVGOI GjLGHjI dajQhS GdJgGH GdcHO GdhHGFj (B)(3g(B(, (3ebG QfI eY ChdFc GdPjf djS dOjge GLSGe eVGOI dajQhS GdJgGH GdcHO GdhHGFj (B)(3g(B.(s
Thesis (M.Sc.)-Cairo University-Faculty of Medicine ,2020.
Bibliography: p. 45-57.
Keywords: Communicable diseases; Liver Transplantation recipients